Dematerialized participation challenges: Methods and practices for online focus groups - Poliandri, Donatella; Perazzolo, Monica; Pillera, Giuseppe Carmelo; Giampietro, Letizia (Frontiers in Sociology, 2023)
This study explores the limitations and benefits of different approaches to conducting online focus groups and illustrates an online focus group protocol used within the Value for Schools project in Italy. According to the project evaluation design, 13 online focus groups were organized, with the participation of 101 teachers and 37 school principals. The protocol setup, incorporation, and reorganization of the indications have been discussed in the literature, addressing the methodological and practical issues, such as the selection of participants and preliminary communication with them; the web conference platform (Zoom Business); timing, as well as access times and mode; the roles of the researchers involved (moderator, co-host technical assistant, co-host-observer, co-host-animator) and their integration spaces; technological support; and animation tools. The recording and transcription tools and subsequent analysis of the textual corpus are presented. Finally, the authors discuss the validation and reliability of online focus group protocols.